Application of the fish associated selected microbes in fish feed useful in enhancing the growth performance of the juvenile tropical Malaysian brown marbled grouper, epinephelus fuscoguttatus - Sukumaran, Mithun (Institut Akuakultur Tropika, 2012)
Brown marbled grouper (BMG)- Epinephelus fuscoguttatus is one of the most important species among the cultured groupers in Malaysia, Indonesia and Thailand.